Changing Epidemiology of Hypoplastic Left Heart Syndrome: Results of a National Swedish Cohort Study. Issue 2 (22nd January 2019) - Öhman, Annika; El‐Segaier, Milad; Bergman, Gunnar; Hanséus, Katarina; Malm, Torsten; Nilsson, Boris; Pivodic, Aldina; Rydberg, Annika; Sonesson, Sven‐Erik; Mellander, Mats
Abstract : Background: Norwood surgery provides a palliative surgical option for hypoplastic left heart syndrome and has been available in Sweden since 1993. The practice of prenatal ultrasound screening was gradually implemented in the same era, resulting in an increased prenatal detection rate. Our primary aims were to study changes in the incidence of live births, prenatal detection rate, and the termination of pregnancies over time. The secondary aims were to study the proportion of live‐borns undergoing surgery and to identify factors that influenced whether surgery was or was not performed. Methods and Results: Neonates with hypoplastic left heart syndrome with aortic atresia born 1990‐2010 were identified through national databases, surgical files, and medical records. The fetal incidence was estimated from the period when prenatal screening was rudimentary. The study period was divided into the presurgical, early surgical, and late surgical periods. The incidence was calculated as the overall yearly incidence for each time period and sex separately. Factors influencing whether surgery was performed were analyzed using Cox‐logistic regression. The incidence at live birth decreased from 15.4 to 8.4 per 100 000. The prenatal detection rate increased from 27% to 63%, and terminations increased from 19% to 56%. The odds of having surgery was higher in the late period and higher in the group with prenatal diagnosis. Conclusions: We observed a decrease in incidence of live‐borns with hypoplastic left heart syndrome aortic atresia. There was in increase in prenatal detection rate and an increase in termination of pregnancy. The proportion of live‐borns who underwent surgery increased between time periods.